Combination of MODIS Vegetation Indices, GRACE Terrestrial Water Storage Changes, and In-Situ Measurements for Drought Assessment in Cagayan River Basin, Philippines - Mae C. Perez, Anjillyn; Blanco, Ariel C. (JNRD - Journal of Natural Resources and Development, 2017)
The Philippines is experiencing recurring drought events accentuated by the increasing incidence of the El Niño phenomenon, particularly due to its position in the equatorial region. To address the negative effects of unpredicted drought events, especially in light of perceptible climate change, the present research developed a methodology for drought assessment in the Cagayan River Basin (CRB) by combining remotely-sensed data including 16-day MODIS Vegetation Indices (VIs) (250 m resolution), monthly Terrestrial Water Storage Changes (TWSC) in 1° grids from NASA’s Gravity Recovery and Climate Experiment (GRACE), and daily in-situ measurements of rainfall and water levels. Time series data of these parameters from 2002 to 2011, a period when major and minor drought events occurred in the country, were statistically analyzed. To smooth out short-term and random variations in the individual time series, a 3-period running average was first applied to each time series. The resulting time series datasets were then subjected to cross-correlation analysis to examine whether the VI anomalies and TWSC values were statistically related to rainfall and water level. The cross-correlation results showed that VI anomalies and TWSC values exhibited strong correlation with in-situ rainfall and water level measurements, having coefficients greater than 0.90 and low time lags ranging from 1 to 3 months during drought events. From this observation, lag-normalized correlation analysis between TWSC and VI anomalies was developed to characterize the onset of drought events and identify drought-prone areas. The majority of the areas identified as susceptible to drought are located in the provinces of Cagayan and Isabela, with areas of 2,596 ha or 68.21 % of the total land area of Cagayan, and 3,751 ha or 56.89 % of the total land area of Isabela. The findings in this research can serve as a basis for proper water resource allocation, especially in the identified drought-prone provinces in the country.